Kepemimpinan dalam Manajemen Mutu Pendidikan: Sebuah Kajian Literatur pada Model Transformasional, Visioner, dan Gaya Kepemimpinan - Azizatun Nisa; Nadiyatul Kholifah; Mu’alimin Mu’alimin (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Leadership and quality management issues in education are important concerns in efforts to improve the quality of educational services and outcomes. Various studies have shown that the quality of principal leadership significantly influences the performance of educational organizations, but a comprehensive synthesis of leadership models and their implementation in quality management is still limited. This article aims to review the literature related to the role of leadership in implementing quality management strategies. The method used is a literature review with a qualitative approach. Data were obtained from Google Scholar and the Publish or Perish application with the keyword